Optimization of the Performance of the Tegal Police Intelligence Unit in the Formation and Development of Intelligence Information Networks to Realize the Maintenance of Public Security and Order - Manggolo, R.Rommy Hero (Advances in Police Science Research Journal, 2024)
The maintenance of security and order is an important part of society. IMP Intelligent Unit is important for early detection, especially in anticipating security and public order disturbances. To support information-gathering efforts, an Intelligence Information Network was established. However, this program could have been more optimal. This program has yet to be optimized at Tegal Police Department. Therefore, this study aims to describe the optimization of the Intelligent Unit Tegal Police Department’s performance in establishing and developing the Intelligence Information Network to realize Harkamtibmas. This research is a descriptive qualitative approach. The type of research is field research. The research location is located at Tegal Police Department. Primary data sources came from interviews and observations, while secondary data sources came from documents and related research. Informants were selected using purposive sampling, including the Intelligent Unit Tegal Police Department ranks and intelligence informants. Triangulation used in this research is the triangulation of methods and data sources. Data processing techniques start from data collection, reduction, presentation, and conclusion drawing. The results of this study indicate that Intelligent Unit in establishing and developing intelligence information networks still needs to be improved, especially in managing resources, technology, budget, and raw materials. The impact on crime control still needs to be improved with sectoral ego between technical functions within the Police Department. Then in the implementation of the program, although it has been adjusted to the SOP, it needs to consider empowering local wisdom. This can build an adaptive intelligence network.